Gør mændene en forskel i børnehaven: Rapport fra et studie af børnehavens pædagogiske kønskarakter - Smeplass, Eli; Olsen, Bent (Kvinder, Køn & Forskning, 2020)
Do men make a difference in kindergartens? Report from a study of the gendered character of the kindergarten. Several kindergarten policies identify men as an exceptional educational resource in kindergartens. An increased male presence supposedly promotes gender equality, as men are thought better suited to meet the gender specific needs of the young boys. We investigate these assumptions in light of a major research project on gender dimensions in female employees’ educational values. Our data consist of answers to a questionnaire from over 700 staff members in all of the 80 kindergartens in two Danish municipalities. The framework of Pierre Bourdieu and Mary Douglas’ Grid Group Cultural Theory informs our theoretical approach. We find that there are no defining differences between women and men’s pedagogical contribution in the kindergarten, in contrary to underlying assumptions of several policy programs. Further, we discuss how these policies contains assumptions of gender essentialism. The discussion addresses how female staff members receives a pedagogical inferior position, while men are favoured for their unique desirable properties, all which are homologous to an increasing polarization between care and economy of the State.